SEISMIC MONITORING OF THE EARTH'S CRUST - Avsjuk Y.N.; Alexandrov S.I.; Gamburtsev A.G.; Gamburtseva N.G.; Nikolaev A.V.; Kiselevitch V.L.; Starodubrovskaya S.P.; Zwang S.L. (My University, 1988)
Systematic observations of wave-velocity changes in the Earth's crust were carried out in Southern Tadjikistan. Observational data obtained in a period of 7 years of seismic wave fields generated by TNT explosions in two natural lakes have been studied. Temporal anomalies of the wave field were shown to be connected with the constructive interference of several periodical components of the process. These anomalies coincide with three strong earthquakes which occurred in the region of the observations. Extrapolation of the temporal variations of the seismic wave-field parameters downward showed a correlation with strong earthquakes that took place during a four-year period.